Swot Analysis in Making Relationship Marketing Program - Muhammad Yusuf; Rahma Saiyed; Josua Sahala (Proceeding of The International Conference on Economics and Business, 2022)
The purpose of this study is to design and determine the relationship marketing strategy at Share Tea Sun Plaza Medan. The analytical method used is descriptive analysis (qualitative), the triangular method, the internal factor matrix (IFE), the external factor matrix (EFE), and a matrix of strengths, weaknesses, opportunities, and threats (SWOT) to create a relationship marketing strategy for the Share Tea Sun Plaza program. Medan. The results of research at Share Tea Sun Plaza Medan show that by using a matrix of internal and external factors and SWOT analysis, a relationship marketing strategy program can be produced that consists of Fresnack Cards, Big Day Sale, and Fresouvenir Cards that will be used in relational marketing.